A survey of methods of assessment of the autonomic system dysfunction in athletes after sport injuries - Wiertel-Krawczuk, Agnieszka; Huber, Juliusz; Hirschfeld, Adam S.; Wojtysiak, Magdalena (Akademia Wychowania Fizycznego w Poznaniu)
This paper is a survey on the neurophysiological techniques supplementary to clinical evaluation of a possible dysautonomia. Sympathetic skin response (SSR) and heart rate variability analysis (RRIV) are neurophysiological tests commonly used in this case. Sports injuries related to the cranio-cerebral spinal cord as well as peripheral nerve trauma can determine the function of the autonomic system. The study aimed to find out the normative values of SSR and RRIV tests, which can be used for diagnosis of patients after sport injuries. SSRs were recorded following an electrical stimulation of the median nerve. RRIV tests were carried out during normal and deep breathing. Twenty young volunteers (aged 23 ± 2.1) were examined in order to estimate the reference values of SSR and R-R interval variation (RRIV) tests and to confirm the lack of functional changes in the autonomic nervous system. SSR and RRIV tests evaluating the function of two different types of effectors should be applied to confirm the presence of dysautonomia, especially in subjects who show unclear clinical symptoms
Keywords: autonomic nervous system; dysautonomia; neurophysiological evaluation; sympathetic skin response; R-R interval variation; sport injuries